(untitled) (Research, Society and Development, 2020)
Jam is the product using fruits added of sugar (sucrose), pectin and acid, in addition to other ingredients. It is of interest to diversify the flavors of this product, as well as to use agro-industrial by-products. The aim of this study was to develop and characterize mixed grape and passion fruit jams of traditional, light and diet formulations. Physicochemical analyzes were performed as pH, moisture content, total acidity, color, soluble solids, and stability after 45 days. The acceptability of the formulations was evaluated by the hedonic scale test. For the soluble solids content, they presented values of 69.67; 45.03 and 32.10 ° Brix, pH values ranged from 3.64 to 3.66, for moisture 27.99; 55.08 and 65.63, for the traditional, light and diet formulations, respectively. The formulations showed difference for the phenolic compounds, and the traditional jam showed higher value (33,38 ± 0,75 mg 100g-1), followed by light light (15,32 ± 0,17 mg 100g-1) and diet (9,79 ± 3,14 mg 100g-1). Sensory acceptance was higher for both traditional and light formulations. During the storage period evaluated, there was no change in acidity values; there was an increase in humidity and changes in color, for all formulations. The results showed the feasibility of using the mixture of grape and passion fruit to make jams with sugar reduction.